2019
DOI: 10.1007/s11465-019-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time task processing method based on edge computing for spinning CPS

Abstract: Spinning production is a typical continuous manufacturing process characterized by high speed and uncertain dynamics. Each manufacturing unit in spinning production produces various real-time tasks, which may affect production efficiency and yarn quality if not processed in time. This paper presents an edge computing-based method that is different from traditional centralized cloud computation because its decentralization characteristics meet the high-speed and high-response requirements of yarn production. Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Unfortunately, deploying ML in an IoT system faces challenges due to constraints of the IoT system. For example, if ML is implemented in the cloud, real-time local decisionmaking [67] is almost impossible to achieve due to underlying limited bandwidth connectivity between sensing nodes and the cloud. To address the problem, ML can be deployed on the device.…”
Section: Edge Computing Based and Machine Learning Enabled Approachesmentioning
confidence: 99%
“…Unfortunately, deploying ML in an IoT system faces challenges due to constraints of the IoT system. For example, if ML is implemented in the cloud, real-time local decisionmaking [67] is almost impossible to achieve due to underlying limited bandwidth connectivity between sensing nodes and the cloud. To address the problem, ML can be deployed on the device.…”
Section: Edge Computing Based and Machine Learning Enabled Approachesmentioning
confidence: 99%
“…Yin et al [28] designed a real-time task processing method using the collaboration of edge computing and CPS. High speed processing and response are the design objective of this collaborative architecture where task and control flow between the communication and CPS layers are handled independently.…”
Section: Related Workmentioning
confidence: 99%
“…In 5G communication technology, vision is the primary application for edge computing. Certain researchers have reported that edge computing can be used for continuous manufacturing processes such as weaving in fiber production and textile manufacturing [44,45].…”
Section: Use Of Edge Computingmentioning
confidence: 99%